OVERALL PERFORMANCE OF THE ELECTRIC ARC MELTING FURNACE DEPENDING ON QUALITY OF FURNACE CHARGE - A. B. Steblov (Литьë и металлургия)
The quality of furnace charge in an electric arc melting furnace to a large extend determines the efficiency of melting. With a tendency of increase of light scrap with a high content of non-iron impurities scrap fine crushing can increase the metallurgical value of scrap and improve technical and economic parameters of electric arc furnace operation.